2008
DOI: 10.1037/1099-9809.14.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well-being in urban adolescents of color.

Abstract: Relationships among predictors and criteria of subjective well-being were examined in a sample of 151 urban adolescents of color, ages 12-15. The relative strengths of family, peer, and school-related support and esteem in predicting three measures of subjective well-being (life satisfaction, positive affect, and negative affect) were explored. Results suggested that sense of worth in one's family explained a significant amount of variance in subjective well-being variables, above and beyond the contributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 66 publications
1
22
0
6
Order By: Relevance
“…A sample item includes “In most ways my life is close to my ideal”, and higher scores indicate high life satisfaction levels. This scale has been found to be a valid and reliable measure among other African American adolescent samples (see Vera et al 2008). …”
Section: Methodsmentioning
confidence: 97%
“…A sample item includes “In most ways my life is close to my ideal”, and higher scores indicate high life satisfaction levels. This scale has been found to be a valid and reliable measure among other African American adolescent samples (see Vera et al 2008). …”
Section: Methodsmentioning
confidence: 97%
“…Scores range from 10 to 50 for each subscale, with higher scores reflecting more frequent emotions in each category. Past research has shown that the PANAS has adequate construct validity (Watson et al, 1988) and acceptable reliability, including studies with samples of diverse adolescents (Crocker, 1997; Huebner & Dew, 1995; Vera et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that there may be ways to enhance SWB by modifying its predictors (e.g., optimism). Enhancing social and familial resources may have the most potential for improving SWB in adolescents (Vera et al, 2008).…”
Section: Subjective Well-being Personality and Family Climatementioning
confidence: 99%